INFUSION THERAPY IN PERI-OPERATIVE PERIOD - V. V. Likhvantsev (Вестник анестезиологии и реаниматологии)
Goal: to familiarize Russian anesthesiologists with the most recent data of the evidence-based medicine about peri-operative infusion therapy. The right choice of the infusion therapy strategy and tactics is a mandatory component of the successful management of the peri-operative period. The most significant changes have recently occurred specifically in this field. First the concept of restrictive tactics of infusion therapy emerged and won its popularity very fast. Then some reasonable doubts appeared about feasibility and safety of using HES solutions. Both affect basic principles of infusion therapy and the recent changes are to be considered from the position of the evidence-based medicine. British and German experts attended these issues and published the relevant guidelines in 2011 and 2016. Comparison and analysis of the implementation opportunities in Russia and recommendations make the subject of this publication. Conclusion: It is necessary to implement the international recommendations for peri-operative infusion therapy with adjustment to relevant Russian regulations in the anesthesiology and intensive care departments.